Factors Considered for the Assessment of Risk in Administrative Review Boards of Canada: A Scoping Review - Jane-Caroline Pellerin; Marie Désilets; Stéphanie Borduas Pagé; Alexandre Hudon (Forensic Sciences)
Background: This scoping review examines the risk factors considered in assessing the dangerousness of individuals found Not Criminally Responsible on Account of Mental Disorder (NCRMD) in Canadian administrative courts. This review aims to identify the factors used by mental health review boards during annual case reviews to guide decisions on detention or release. Methods: Using a scoping review approach following PRISMA guidelines, this study analyzed research across multiple databases to identify relevant studies focusing on risk assessment for NCRMD cases. Results: The findings indicate that five primary categories of risk factors—historical, clinical, behavioral, legal, and miscellaneous—are influential in the decision-making process. Historical factors, such as past violence and early psychiatric contacts, are critical in predicting future risk. Clinical factors, including psychiatric diagnosis and treatment adherence, are key to evaluating current and potential future risks. This study reveals variability in the application of standardized risk assessment tools, highlighting a need for more consistent practices across Canadian jurisdictions. Conclusion: This review concludes that, while a multifaceted approach to risk assessment is essential for balancing public safety with individual rehabilitation, further research is needed to refine these processes and establish more uniform standards for managing NCRMD cases in forensic psychiatry.